IMPDH1, a prognostic biomarker and immunotherapy target that correlates with tumor immune microenvironment in pan-cancer and hepatocellular carcinoma - Liu, Chengdong; Zhang, Wanli; Zhou, Xiaohan; Liu, Li (Frontiers in Immunology, 2022)
IMPDH1, a rate-limiting enzyme in de novos synthesis of guanine nucleotides, plays an essential role in the growth and progression of certain tumors. However, there is still a lack of study on IMPDH1 evaluating its role in the tumor immune microenvironment, the potential mechanisms, and its potential as a promising tumor therapeutic target. Therefore, in order to further clarify the above doubts, databases and data analysis tools: The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), Genotype-Tissue Expression (GTEx), TIMER2.0, KM-Plotter, University of Alabama at Birmingham Cancer data analysis Portal (UALCAN), cbioportal, The Human Protein Atlas (HPA), and Gene Expression Profiling Interactive Analysis 2 (GEPIA2) were used to perform the systematic analysis of IMPDH1, including mRNA expression, protein expression, prognostic value, Enrichment analysis, DNA methylation, immune cell infiltration in pan-cancer. Then, we conducted qRT-PCR to analyze the expression level of IMPDH1 in cancer tissues and non-cancer tissues of patients with primary hepatocellular carcinoma (HCC), and performed the same verification at cellular level. We discovered that IMPDH1 was highly expressed in a variety of tumors and was associated with poor prognosis. IMPDH1 not only had the potential as a tumor prognostic marker and therapeutic target, but also was closely related to immune cells, immune checkpoints and immune-related genes and pathways in the tumor immune microenvironment(TIME). Meanwhile, IMPDH1 expression influenced the efficacy and prognosis of tumor patients treated with immune checkpoint inhibitors. IMPDH1 may be as a potential combined target of immunotherapy.